Hazardous holiday - Johnson, Liz, 1981- (Johnson, Liz, 1981- Men of valor., 2016)
"Just in time for the holidays, navy SEAL Zach McCloud returns home from deployment--and discovers someone wants his family dead. When he married his cousin's struggling widow, he vowed to help her and her seriously ill son, and now he'll risk everything to protect them. Even if their arrangement is only temporary. Kristi's certain an unhappy client from the law firm where she works is determined to hunt her down. But when a sniper bullet wildly misses its target, they begin to question whether it's really her someone wants dead. Working together, can they figure out why they've been attacked...and keep little Cody from the nefarious forces dead set on making this Christmas their last?"--Page 4 of cover.